Endocardial ablation of ventricular tachycardia ablation in arrhythmogenic right ventricular cardiomyopathy aiming epicardial late potential abolition. (19th May 2022) - Waintraub, X; Sauve, R; Vedrenne, G; Amet, D; Gras, M; Degand, B; Moini, C; Duthoit, G; Laredo, M; Badenco, N; Lesaffre, F; Lepillier, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Catheter ablation is frequently needed to treat ventricular tachycardia (VT) in ARVC patients. Ablation aiming non-inducibility (NI) and late potential (LP) abolition has been shown to be effective1. Simultaneous endo-epicardial mapping demonstrate epicardial involvement in most VT2. However epicardial fat and vicinity of coronary artery may prevent effective epicardial ablation. Aims: (a) evaluate endocardial-only ablation guided by epicardial late-potential recording (EA-ELP) to achieve LP abolition (LPA) and NI; (b) measure ablation-index(AI) values allowing epicardial LP suppression by endocardial ablation, as a surrogate for transmurality. Methods: From 2019 to 2021 the authors (XW, EG) evaluated EA-ELP in ARVC patients patient referred for ablation. Our ablation protocol was previously described3. Endo and epicardial voltage mapping of the right ventricle (RV) were performed in sinus rhythm using 0.5-1.5 mV threshlods for endocardial scar and 0.5-1 mV for the epicardial. All LP were manually tagged. Programmed ventricular stimulation (PVS) was performed till S4 from the RV apex and other sites, all inducible tolerated VT were mapped. Endocardial ablation was performed with an irrigated tip catheter positioned in front of epi-LP recorded by a multi-electrode catheter aiming to eliminate or delay epi-LP as a surrogate for transmurality. For each lesion fulfilling the «transmurality criteria», the AI values were recorded. Remap was performed to validate LPA and NI was tested. Patient follow-up (FU) rely on telemonitoring in ICD-carriers and holter/exercise test for the others. Results: 11 patients were enrolled (9M/2F, mean age 45 years), 9 for VT recurrence (3 redo) and 2 for de novo VT. The median ICD therapy before ablation was 5/patient (mean 1.7). The clinical VT originated from the RV outflow tract (RVOT) in 5 patients, peritricuspid (PT) in 2, RV free wall (RFW) in 4. Substrate were more extended in the epicardium compared to the endocardium: epi-LP and scar surfaces were 42.5 cm2/118 cm2 versus 24.5 cm2/25.5 cm2 for the endocardium. In one patient, additional epicardial lesion was necessary to achieve LPA. The mean ablation duration was 3377 s. Remap showed LPA in all patients and PVS was negative in all (not tested in one due to hemodynamic instability). One patient presented retrosternal hematoma after ablation with spontaneous favorable outcome. Endocardial AI values allowing epi-LP abolition were 595 for the inferior wall, 625 in the RVOT, 604 for PT and 639 for RFW. During a mean FU of 12 months (median 16.5 mths), only one patient had VT recurrence. Conclusion: Based on this case-series, EA-ELP appeared as a safe and effective method to treat VT in ARVC. EA-ELP ablation allowed VT suppression in 91 % of patients after an mean FU of 12 mths. The RV endocardial AI needed to suppress epi-LP ranged was between 595-639 and could be used as surrogate for transmurality in ARVC.